Obesity-Related Differences between Women and Men in Brain Structure and Goal-Directed Behavior - Horstmann, Annette; Busse, Franziska; Mathar, David; Mueller, Karsten; Lepsien, Joeran; Schloegl, Haiko; Kabisch, Stefan; Kratzsch, Juergen; Neumann, Jane; Stumvoll, Michael; Villringer, Arno; Pleger, Burkhard (Frontiers in Human Neuroscience, 2011)
Gender differences in the regulation of body weight are well documented. Here, we assessed obesity-related influences of gender on brain structure as well as performance in the Iowa Gambling Task. This task requires evaluation of both immediate rewards and long-term outcomes and thus mirrors the trade-off between immediate reward from eating and the long-term effect of overeating on body weight. In women, but not in men, we show that the preference for salient immediate rewards in the face of negative long-term consequences is higher in obese than in lean subjects. In addition, we report structural differences in the left dorsal striatum (i.e. putamen) and right dorsolateral prefrontal cortex for women only. Functionally, both regions are known to play complimentary roles in habitual and goal-directed control of behavior in motivational contexts. For women as well as men, gray matter volume correlates positively with measures of obesity in regions coding the value and saliency of food (i.e. nucleus accumbens, orbitofrontal cortex) as well as in the hypothalamus (i.e. the brain's central homeostatic centre). These differences between lean and obese subjects in hedonic and homeostatic control systems may reflect a bias in eating behavior towards energy intake exceeding the actual homeostatic demand. Although we cannot infer from our results the etiology of the observed structural differences, our results resemble neural and behavioral differences well known from other forms of addiction, however, with marked differences between women and men. These findings are important for designing gender-appropriate treatments of obesity and possibly its recognition as a form of addiction.